The body as a plastic work: Catherine Malabou e le metamorfosi del corporeo - Maggiore, Valeria (Scenari, 2021)
Performance art (like Orlan’s “Carnal Art”) involves artist body in the performance itself and it is based on a clear phenomenological assumption: we “do not have” a body, but we “are” our body, we are our “sculpture”. Fascinated by the enigmas of change, Aesthetics has sought to address the metaphysical question concerning metamorphosis and the problem of identity persistence in change; the solution has been found for centuries in the opposition between essence and appearance: as highlighted by fantastic literature (Ovid, Apuleius, Kafka), in metamorphosis the “substance” remains unchanged and only appearance (or accident) changes. However, the reflection carried out by Catherine Malabou on the problem of construction and deconstruction of individual identity offers an original perspective on the relationship between form and accident, starting from a new interpretation of the concept of “plasticity”. In this article we propose to investigate the relationship between “visible body” and “lived experience” in a constant dialogue between phenomenological theses, art and literature.